Perioperatif effects of epidural administration of morphine and midazolam in children [Çocuklarda epidural yolla uygulanan morfin ve midazolamin perioperatif etkileri] - (:unkn) unknown (My University, 2003)
In our study we aimed to compare the effects of midazolam and morphine administered by epidural route on intraoperative inhalational anaesthetic requirement and postoperative analgesic efficiency and adverse effects. 40 patients between 1.5-14 years of age in ASA I physical status were randomly allocated in one of two groups. The baseline values of systolic arterial pressure (SAP), diastolic arterial pressure (DAP) and heart rate (HR) were recorded. Induction and maintenanee of anaesthesia was performed with halothane in N2-O2 mixture. Morphine HCL 0.1 mgkg-1 to group M (n=20) and midazolam 0.05 mgkg-1 to group D (n=20) was given by epidural route in a total volume of 0.2 mLkg-1. SAP, DAP, HR and halothane concentration values, were recorded every 5 minutes in the first 30 minutes and every 15 minutes thereafter. At the 1st, 2nd, 4th and 24th hours after the extubation, using a pain evaluation scale (PES), the numerical value ranging between 0 and 100, corresponding to the respective facial expression was recorded. At the above mentioned hours, sedation score, respiratory rate, sensorial block level by pinprick test, complications like nausea, vomiting, flushing, itching, urinary retention and respiratory depression were recorded. At the 24th hour, the patients who can be communicated with were asked whether they remembered the pinprick test performed the day before. The time of first analgesic requirement was also recorded. PES and sedation score values at the 1st and 2nd postoperative hours were significantly lower in morphine group and the incidence of itching was significantly higher in morphine group throughout the follow-up. The incidence of vomiting was higher in morphine group at the 4th and 24th hours. There was no significant difference between the groups concerning the other parameters followed. It was concluded that epidurally injected single-dose morphine provided more effective analgesia and sedation during the first two postoperative hours compared to midazolam, and there was no difference between the groups concerning those parameters at the other follow-up hours.
Keywords: Children; Epidural analgesia; Midazolam; Morphine; Perioperative